Synthesis of Zn-Co-TiO2 nanocomposite coatings by electrodeposition with photocatalytic and antifungal activities - Reisi Nafchi, Mehdi; Ebrahimi-kahrizsangi, Reza (Journal of Composites and Compounds, 2021)
TiO2 has become the most well-known photocatalysts for solving environmental problems as a wide-band n-type semiconductor. This research aimed to coat a carbon steel substrate with Zn-Co-TiO2 nanocomposite via the electrodeposition method. Scanning electron microscopy (SEM) was used to examine the microstructure, (energy-dispersive X-ray spectroscopy) EDS analysis was used to examine the composition of the coating, and a pull-off test was used to determine the adhesion of the coating. In this regard, the electrodeposition of the coatings was carried out at the optimum conditions of 0.1 A, the concentration of TiO2 equal to 15 g/L, deposition time of 20 min, the temperature of 25.5 °C, and pH of 5-5.5 in different electrolyte compositions. Also, the photocatalytic properties of TiO2 were determined by the fungal growth on the sample surface. According to the results, the fungal growth was reduced with the increase in the TiO2 content in the coating.